2018
DOI: 10.1515/cclm-2017-0796
|View full text |Cite
|
Sign up to set email alerts
|

The quest for equivalence of test results: the pilgrimage of the Dutch Calibration 2.000 program for metrological traceability

Abstract: Calibration 2.000 was initiated 20 years ago for standardization and harmonization of medical tests. The program also intended to evaluate adequate implementation of the In Vitro Diagnostics (IVD) 98/79/EC directive, in order to ensure that medical tests are fit-for-clinical purpose. The Calibration 2.000 initiative led to ongoing verification of test standardization and harmonization in the Netherlands using commutable external quality assessment (EQA)-tools and a type 1 EQA-design, where feasible. National s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Although out of scope for the original C37 protocol, literature reports starting with the C37 protocol or very similar protocols have shown that supplementing a serum pool with a number of analytes has produced pools with elevated concentrations with acceptable commutability properties [11,12].…”
Section: Blood Collection and Processing Proceduresmentioning
confidence: 99%
“…Although out of scope for the original C37 protocol, literature reports starting with the C37 protocol or very similar protocols have shown that supplementing a serum pool with a number of analytes has produced pools with elevated concentrations with acceptable commutability properties [11,12].…”
Section: Blood Collection and Processing Proceduresmentioning
confidence: 99%
“…Unfortunately, with the exception of a few examples [10][11][12][13][14], category 1 schemes remain scarce and so the real benefit of participation in EQAS remains modest. Other areas of laboratory medicine, where the experience of EQAS is more recent and/or deals with different type of measures, seem to benefit more from the participation in EQAS as reported for immunophenotyping [15] or microbiology [16].…”
Section: Present Situationmentioning
confidence: 99%
“…In the Netherlands, the Calibration 2.000 initiative is a nationwide program, established in 1998, which strived for either standardization or harmonization of tests in domains beyond clinical chemistry such as hematology, endocrinology, coagulation, immunology, TDM, parasitology, etc. [11]. The output of its research was fed into the EQAS of the Dutch SKML and is reviewed in this special issue [11].…”
Section: Present Situationmentioning
confidence: 99%
“…Since 1947, attempts have been made to improve interlaboratory comparability of test results. History and updates have been described by renowned authors in recent editorials or other peer-reviewed literature [6][7][8][9]. Notwithstanding major scientific advances, appearance of international guidelines (global harmonization task force, ISO-guidelines, …) and landmark legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%